The Use of Flashcard Games in the Application of Cognitive Behavior Therapy (CBT) in Schizophrenic Patients with Risk of Violent Behavior (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
The increase in maladaptive behavior of schizophrenic patients in recent times, such as violent behavior, hitting people, breaking things until they commit a murder, has been troubling for the community. This situation is a serious concern for all parties, especially health workers, to provide comprehensive and effective mental nursing care management in reducing the symptoms of maladaptive behavior. Group therapy based on Cognitive Behavior Therapy (CBT) with Flashcard media is one of the development and innovation models of psychotherapy that can be useful in overcoming violent behavior in schizophrenia patients. This study was aimed to determine the effectiveness of CBT with flashcards on changes in violent behavior in schizophrenic patients. The research design was used a quasi-experimental pre-posttest with a control group. A sample of 50 people includes 25 people in the intervention group and 25people in the control group. The results were showed that the reduction in signs and symptoms of schizophrenic patients was greater in the intervention group than in the control group, with a value of p=0,000. The CBT therapy with flashcards was effective 66.6% in reducing violent behavior. CBT therapy with flashcards is recommended to be applied as effective, efficient, and easy therapy for health professionals and families to reduce violent behavior.